2019
DOI: 10.3390/atmos10070376
|View full text |Cite
|
Sign up to set email alerts
|

Objective Center-Finding Algorithm for Tropical Cyclones in Numerical Models

Abstract: Precise center-detection of tropical cyclones (TCs) is critical for dynamic analysis in high resolution model data. The existence of both smaller scale perturbations and larger scale circulations could reduce the accuracy of center positioning. In this study, an objective center-finding algorithm is developed based on a two-dimensional Fourier filter and a vorticity centroid algorithm. This proposed algorithm is able to automatically adjust its parameters according to the scale of the target vortex instead of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…But, when the morphological structure characteristics of tropical cyclone are not obvious, the morphological model analysis method cannot locate the center of tropical cyclone. The wind field analysis method is to locate the center of tropical cyclone according to the characteristics of cyclone [22,23]. The minimum wind speed and the maximum vorticity are the central features of the tropical cyclone.…”
Section: Introductionmentioning
confidence: 99%
“…But, when the morphological structure characteristics of tropical cyclone are not obvious, the morphological model analysis method cannot locate the center of tropical cyclone. The wind field analysis method is to locate the center of tropical cyclone according to the characteristics of cyclone [22,23]. The minimum wind speed and the maximum vorticity are the central features of the tropical cyclone.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the influence of clouds and rain belts around the wind eye on the positioning process, the experimental results for infrared satellite cloud images indicated that the best average error of the model in the longitude and latitude directions reached 0.12238 (approximately 13.58 km). Zhao et al (2019) used the centroid algorithm from two-dimensional Fourier filtering to detect potential cyclone vortices based on eliminating small-scale perturbations and finally calculated the vortex center. The advantage of this algorithm is that the parameters are automatically adjusted according to the size of the target vortex.…”
Section: Introductionmentioning
confidence: 99%
“…The second kind of method is based on the wind field analysis [ 21 , 22 ]. The center of tropical cyclone is determined by finding the minimum value of wind speed or the maximum value of cyclone vortices [ 23 ].…”
Section: Introductionmentioning
confidence: 99%